ASSISTANCE TO SUICIDE ATTEMPTS IN ADOLESCENCE IN EMERGENCY SERVICES: THE PERFORMANCE OF HEALTH PROFESSIONALS, CHALLENGES AND ASSOCIATED FACTORS (CIPEEX, 2025)
Suicide is considered a public health priority by PAHO/WHO and is among the leading causes of death among adolescents aged 15 to 19. This phenomenon stems from social, cultural, biological, and emotional factors, such as family conflicts, depression, and academic difficulties, which increase vulnerability, especially given the biopsychosocial changes inherent to adolescence. Social and family support is an important protective factor, while a lack of support can increase the risk of suicidal behavior. This study aimed to analyze the actions of health professionals in emergency and urgent care services when faced with adolescent suicide attempts. This is an integrative literature review, conducted based on searches in national and international databases, such as BVS, SciELO, CINAHL, PubMed, and EBSCO, as well as official websites, including articles published between 2012 and 2024 in Portuguese, English, Spanish, and Turkish. It was evident that adolescence is a phase marked by transformations that can intensify vulnerability to suicide, reinforcing the importance of ethical, empathetic, and humane care by health professionals. These professionals face challenges in overcoming taboos, requiring specific protocols and integrated multidisciplinary work that considers clinical, psychological, family, social, and cultural aspects. The role of emergency services in early identification and immediate intervention stands out, preventing deaths and ensuring referral for continued care in UBS, CAPS, UPA, SAMU, and support from services such as CVV. It is concluded that suicide attempts in adolescence constitute a serious public health problem, requiring intersectoral strategies, strengthening of support networks, prevention campaigns such as Yellow September, and new studies that contribute to standardizing and improving care.
Keywords: Suicide; adolescent; health professional